Effect of microwave treatment on metal-alginate beads - Campañone, Laura Analia (2014)
Encapsulation is defined as a technique to protect solid, liquid or gaseous active compounds from interacting with the environment. Encapsulated minerals may be incorporated into food products submitted to microwave heating, thus it is interesting to study their interaction with microwaves due to the relevant dielectric properties of the ions during heating. In the present work, zinc sulphate heptahydrate, ferrous sulphate heptahydrate, calcium chloride and sodium alginate were used to test metal ion-alginate beads under microwave heating. The objective was to compare the behavior of free ions in solution with those trapped within the alginate matrix while being submitted to electromagnetic radiation. The beads were characterized before and after heating by texture profiles, differential scanning calorimetry and infrared spectroscopy (FTIR). During microwave heating, the presence of zinc and iron increased the inner temperature of the system; however calcium did not show the same behavior. These differences were attributed to the microstructure of the beads.